Peat as a carbon source for non-platinum group metal oxygen electrocatalysts and AEMFC cathodes. (1st May 2022) - Teppor, Patrick; Jäger, Rutha; Paalo, Maarja; Adamson, Anu; Härmas, Meelis; Volobujeva, Olga; Aruväli, Jaan; Palm, Rasmus; Lust, Enn
Abstract: Naturally abundant well-decomposed peat was used as a precursor for synthesizing several non-platinum group metal-type oxygen electrocatalysts. The materials were studied in an alkaline environment, where it was discovered that the oxygen evolution (OER) and the oxygen reduction (ORR) activity of the catalysts can be severely influenced by changing the parameters of the peat carbonization procedure. High OER activity was achieved with a minimally treated catalyst which seemed to be because of a Co-rich FeCo alloy species. In both rotating disc electrode and anion exchange membrane fuel cell experiments, the catalyst based on ZnCl2 -activated peat-derived carbon showed superior ORR performance with a peak power density of 51 mW cm −2 . It was found that the peak power densities of the catalysts correlated with several physical parameters. Above all, we demonstrate the possibility of fabricating advanced functional carbon materials for oxygen electrocatalysis from peat. Graphical abstract: Image 1 Highlights: Bifunctional platinum-free oxygen catalysts prepared from abundant decomposed peat. Physical and catalytical properties can be tuned by modifying synthesis conditions. Correlations between particle size properties and AEMFC performance established.